Analysis of Factors Causing Pre-Eclampsia-Related Events at Mokopido Hospital - Musdalifah, Musdalifah (Jurnal Indonesia Sosial Sains, 2024)
Preeclampsi is a condition that becomes a fear during pregnancy because it will cause problems for the mother and child to lead to death in one of them or sequelae that will be suffered by the mother after giving birth. Research is needed to prevent causes from emerging that have an impact on increasing preeclampsi so that appropriate governance can be established according to the priority of the problems found. At Mokopido Hospital, there are still patients with preeclampsi although in 2021 there were 129 patients, to 2022 there were 109 patients, there was a decrease of 20 patients. This study aims to determine the factors associated with the incidence of preeclampsia at Mokopido Hospital. This study used a cross sectional study with secondary hospital data. The results of simultaneous f and partial t tests found that age, educational status, body mass index and parity history were associated with the incidence of preeclampsia. Dominated by body mass index and age during pregnancy